2003
DOI: 10.1038/sj.onc.1206537
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comparison of human keratinocyte and squamous cell carcinoma responses to UVB irradiation: implications for skin and epithelial cancer

Abstract: To gain insight into the transformation of epidermal cells into squamous carcinoma cells (SCC), we compared the response to ultraviolet B radiation (UVB) of normal human epidermal keratinocytes (NHEK) versus their transformed counterpart, SCC, using biological and molecular profiling. DNA microarray analyses (Affymetrix s , B12 000 genes) indicated that the major group of upregulated genes in keratinocytes fall into three categories: (i) antiapoptotic and cell survival factors, including chemokines of the CXC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 57 publications
(50 reference statements)
13
73
0
3
Order By: Relevance
“…As expected for a mutant p53 protein, no modification of its expression was found in response to cisplatin (Figure 6a). We found that while p73-mediated growth arrest and apoptotic target genes p21 waf1 , bax, p53AIP1, pig-3 were induced upon cisplatin treatment, S100A2 mRNA and protein, in agreement with previously reported findings (Dazard et al, 2003), were downregulated (Figure 6a-c). Similar findings were obtained upon treatment of HaCaT cells with doxorubicin (data not shown).…”
Section: S100a2 Expression Is Induced During Keratinocyte Differentiasupporting
confidence: 81%
“…As expected for a mutant p53 protein, no modification of its expression was found in response to cisplatin (Figure 6a). We found that while p73-mediated growth arrest and apoptotic target genes p21 waf1 , bax, p53AIP1, pig-3 were induced upon cisplatin treatment, S100A2 mRNA and protein, in agreement with previously reported findings (Dazard et al, 2003), were downregulated (Figure 6a-c). Similar findings were obtained upon treatment of HaCaT cells with doxorubicin (data not shown).…”
Section: S100a2 Expression Is Induced During Keratinocyte Differentiasupporting
confidence: 81%
“…Even in the absence of p53, the same gene size relationship exists for UV-induced genes (109). Compact p53-independent UV-induced genes included AP-1 responsive immediate early genes, NFjB-regulated cytokines and histones (1,29,48,55,168). Therefore, UV-induced genes tend to be compact, regardless of the transcription factor driving expression.…”
Section: Uv Ddr the Transcription Paradox And Gene Sizementioning
confidence: 95%
“…Beside their constitutive expression in myeloid cells, they are expressed in epithelial cells in response to stress [14,15]. Their expression is transiently induced in keratinocytes after epidermal injury [16,17], after UVB irradiation [18], and in response to proinflammatory cytokines such as TNFa and IL1b [14]. Data showing that the two S100 proteins are up regulated by the putative TLR ligand LPS are conflicting [19,20].…”
Section: Introductionmentioning
confidence: 99%